Implementation of the SIWI Learning Strategy to Encourage Deaf Students' Writing Skills At Extraordinary School (SLB) Lamongan - Khoirul Huda; Oikurema Purwati; Pratiwi Retnaningdyah (CV. AFDIFAL MAJU BERKAH, 2023)
This article focuses on answering questions regarding the SIWI implementation strategy for deaf children in Lamongan. This is because there are deaf children in the Lamongan SLB school who have difficulty receiving teacher instructions so that it is more difficult to learn to write. Given the importance of writing for deaf students, of course the teacher must find a solution, one of which can be using the SIWI strategy to spur deaf students' writing skills. So in this article we will look at the implementation of the SIWI strategy by classroom teachers to improve the writing skills of deaf students. This research is a type of qualitative research using a phenomenological approach. This aims to photograph the SIWI implementation strategy in Lamongan SLB. Data collection in this study used two techniques, namely interviews and field observations. The results of this study indicate the effectiveness of applying the SIWI strategy in class during the learning process at SL Lamongan and indications that SIWI can be applied properly so as to encourage the improvement of deaf students' ability to write.